Gray/White Matter Contrast in Parkinson’s Disease - Uribe, Carme; Segura, Barbara; Baggio, Hugo C.; Abos, Alexandra; Garcia-Diaz, Anna I.; Campabadal, Anna; Marti, Maria J.; Valldeoriola, Francesc; Compta, Yaroslau; Bargallo, Nuria; Junque, Carme (Frontiers in Aging Neuroscience, 2018)
Gray/white matter contrast (GWC) decreases with aging and has been found to be a useful MRI biomarker in Alzheimer’s disease, but its utility in Parkinson’s disease (PD) patients has not been investigated. The aims of the study were to test whether GWC is sensitive to aging changes in PD patients, if PD patients differ from healthy controls in GWC, and whether the use of GWC data would improve the sensitivity of cortical thickness analyses to differentiate PD patients from controls. Using T1-weighted structural images, we obtained individual cortical thickness and GWC values from a sample of 90 PD patients and 27 controls. Images were processed with the automated FreeSurfer stream. GWC was computed by dividing the white matter by the gray matter values and projecting the ratios onto a common surface. The sample characteristics were: 52 patients and 14 controls were males; mean age of 64.4±10.6 years in PD and 64.7±8.6 years in controls; 8.0±5.6 years of disease evolution; 15.6±9.8 UPDRS; and a range of 1.5 to 3 in Hoehn and Yahr stage. In both PD and controls we observed significant correlations between GWC and age involving almost the entire cortex. When applying a stringent cluster-forming threshold of p<0.0001, the correlation between GWC and age also involved the entire cortex in the PD group; in the control group, the correlation was found in the parahippocampal gyrus and widespread frontal and parietal areas. The GWC of PD patients did not differ from controls’, whereas cortical thickness analyses showed thinning in temporal and parietal cortices in the PD group. Cortical thinning remained unchanged after adjusting for GWC. GWC is a very sensitive measure for detecting aging effects, but did not provide additional information over other parameters of atrophy in PD.